2013
DOI: 10.4049/jimmunol.1201218
|View full text |Cite
|
Sign up to set email alerts
|

IL-2R Signaling Is Essential for Functional Maturation of Regulatory T Cells during Thymic Development

Abstract: CD4+ Foxp3+ Tregs are an independent cell lineage and their developmental progression during thymic development depends on IL-2R signaling. However, the role of IL-2R signaling during thymic Treg development remains only partially understood. The current study assessed the contribution of IL-2 in the expansion and functional programming of developing Tregs. In the absence of IL-2Rβ signaling, predominately CD4+ CD25- Foxp3lo T cells were found and these cells exhibited somewhat lower expression of the prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
81
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 40 publications
(61 reference statements)
6
81
0
1
Order By: Relevance
“…Furthermore, STAT5 binds to the conserved sites within the Foxp3 promoter, and then STAT5 signaling regulates Foxp3 expression (42,43). Our data showed that Socs1 expression in IL-2-stimulated Treg cells of RORgt Tg mice was significantly higher than in that of C57BL/6 mice.…”
Section: Foxp3supporting
confidence: 49%
“…Furthermore, STAT5 binds to the conserved sites within the Foxp3 promoter, and then STAT5 signaling regulates Foxp3 expression (42,43). Our data showed that Socs1 expression in IL-2-stimulated Treg cells of RORgt Tg mice was significantly higher than in that of C57BL/6 mice.…”
Section: Foxp3supporting
confidence: 49%
“…CD4 1 CD8 1 thymocytes interact with class II MHC-expressing cells in the medullar and Hassall's corpuscles of thymus, where thymic stromal lymphopoietin promotes myeloid and plasmacytoid dendritic cells that induce Tregs (75). Treg induction requires TGF-b, stimulation of CD28 by B7.2, and IL-2 activating the IL-2R to induce Stat5 and FOXP3 (76). FOXP3 induces CD25 and inhibits IL-2 expression.…”
Section: Professional Spies-tregsmentioning
confidence: 99%
“…At the earliest stage of the development, IL-2 engagement in the thymus promotes expression of Foxp3 in developing CD4 + T cells, contributing to the development of mature and functional tTregs [29,63,64]. In the periphery, further IL-2/IL-2R interactions are required to maintain the competitive fitness of the tTreg pool [6567].…”
Section: Il-2 and Treg Homeostasismentioning
confidence: 99%
“…Interestingly, some Foxp3-expressing cells are still detected in IL-2- and IL-2rα-deficient mice despite the lack of IL-2 signaling [65,66], most likely due to the redundant capacity of IL-7 and IL-15 to activate Stat5 and partially compensate for the absence of IL-2/IL-2R interactions [72,73]. However, these cells express lower levels of Foxp3 and other key Treg functional molecules, including CTLA-4, and demonstrate poor competitive fitness and function when compared with Tregs developing in wild-type animals [29,65,66]. This supports an essential and non-redundant role for IL-2 in promoting Treg homeostasis and function.…”
Section: Il-2 and Treg Homeostasismentioning
confidence: 99%
See 1 more Smart Citation